Oral health providers and secondary prevention of disordered eating: an application of the transtheoretical model. - DeBate RD; Tedesco LA; Kerschbaum WE (Journal of Dental Hygiene)
Purpose: Although oral health providers have an important role in early identification, referral, and case management of patients with eating disorders, little is reported regarding their current secondary prevention practices. The purpose of this study was to assess readiness among dentists and dental hygienists pertaining to secondary prevention of disordered eating among their patients.Methods:This study employed a randomized cross-sectional study. Data were collected from 207 dentists and 369 dental hygienists using a self-administered paper and pencil questionnaire. The questionnaire included items derived from constructs from the Transtheoretical Model in addition to demographic information. Five criterion-specific secondary prevention behaviors were assessed with regard to eating disorders: identification of oral manifestations, addressing concerns, prescribing oral treatment, patient referral, and case management.Results:Generally speaking, the majority of responding dentists and dental hygienists were observed to be in a low state of readiness with regard to the five criterion-specific behaviors. Less than 33% of responding dentists and 43% of dental hygienists reported that they assessed patients for disordered eating, and only 42% of dentists and 44% of dental hygienists prescribed specific home oral health care instructions for patients suspected of eating disorders. Less than 21% of dentists and 20% of dental hygienists currently arranged a more frequent recall program, while less than 20% of dentists and 17% of dental hygienists reported that they referred patients with oral manifestations of eating disorders for treatment. Only 13% of responding dentists and 7% of dental hygienists reported communicating with the patient's primary care provider. Statistically significant differences were observed among oral health providers with regard to assessing their patients for disordered eating (p = .006) and communicating with the patients' primary care providers (p < .001). In general, more dental hygienists indicated assessing patients for oral manifestations of disordered eating, while more dentists reported communicating with their patients' primary care providers.Conclusions: Engaging the oral health care provider in secondary prevention of eating disorders is important for decreasing the potential for further damage to the teeth and oral tissue, as well as improving the patient's overall health and quality of life. Although both dentists and dental hygienists play important roles in secondary prevention of eating disorders, increasing the number who engage in consistent secondary prevention practices is essential. Increasing the involvement of oral health care providers in secondary prevention behaviors will involve movement along the continuum of stages (pre-contemplation to contemplation to action to maintenance), while also understanding that movement may take time and involve regression along the way.